It's up to you, New York : will Holly find love in the city where dreams are made? - Daly, Tess (Coronet, 2013)
Will Holly find love in the city where dreams are made? Fielding calls from disgruntled customers on a crispbread telesales careline isn't exactly where Holly Collins saw herself in life. Living in a shoebox flat and working in a windowless building on an outer London industrial estate were never quite what she'd had in mind. So when Holly is picked from obscurity to take part in Street Scout, a television series on the hunt for fashion's next big model, life finally seems to be taking a turn for the better for the happy-go-lucky twenty-something. Surely this is her big moment? But Holly knows only too well that dreams are just that and when it feels like everything - and everybody - is conspiring against her, Holly heads for New York with her best friend Meg. The magic of Manhattan has Holly in its grasp: strutting down 5th Avenue and drinking two too many cosmopolitans, taking romantic carriage rides in Central Park and standing at the top of the Empire State building she can scarcely believe how far away the real world seems. But when Holly is faced with the biggest decision of her life can she make the fairy tale become a reality?